2008
DOI: 10.1007/s11104-008-9669-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sorghum seedlings, and previous crop, on soil fluorescent Pseudomonas spp.

Abstract: Hypotheses in which sorghum seedlings [Sorghum bicolor (L.) Moench] of different genotypes will differentially modify soil microorganisms and will affect subsequent planting of wheat (Triticum aestivum L.) seedlings, were tested. Wheat cultivar Lewjain, and sorghum genotypes Redlan and RTx433, were planted into soils previously planted with wheat or sorghum in growth chamber experiments. Total culturable fungi and oomycetes, and fluorescent Pseudomonas spp. numbers (cfu) were determined. Pseudomonads were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 59 publications
1
15
0
1
Order By: Relevance
“…Any changes to the microbial community are attributed to changes in organic root exudates affecting microbial activity in a species-specific manner (18,51). In this study, these changes were detected in the bulk soil and were apparent even though the crop was the same in both rotations in the sampling year.…”
Section: Discussionmentioning
confidence: 55%
“…Any changes to the microbial community are attributed to changes in organic root exudates affecting microbial activity in a species-specific manner (18,51). In this study, these changes were detected in the bulk soil and were apparent even though the crop was the same in both rotations in the sampling year.…”
Section: Discussionmentioning
confidence: 55%
“…Recently, we provided evidence suggesting that when sorghum seedlings preceded wheat seedlings in a crop sequence, sorghum genotype influenced the characteristics of fluorescent Pseudomonas spp. populations in bulk soil (Funnell-Harris et al 2008). That root exudates of sorghum genotypes Redlan and RTx433 differed had been shown by studies in which seedlings differentially produced the benzoquinone root exudate, sorgoleone: of 25 genotypes tested, Redlan produced the greatest amount while RTx433 produced the least (approx.…”
Section: Introductionmentioning
confidence: 96%
“…18 versus 1 mg per g root fresh weight) (Nimbal et al 1996). Although this compound is technically challenging to detect in rhizospheres of soil-grown plants (Weidenhamer 2005), previous studies have suggested that genotypespecific differences in sorghum root exudates may affect soil microbial communities (Kipe-Nolt et al 1985;Funnell-Harris et al 2008). The turnover of applied sorgoleone to native soils indicated that microorganisms utilize this compound as an energy source, which suggests a possible mechanism of how sorgoleone may influence soil microbial communities (Gimsing et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabólitos secundários que são depositados no solo pelos exsudados ou pela morte das plantas fornecem uma rica fonte de carbono que é utilizada por populações microbianas do solo (belz, 2007). Esses metabólitos influenciam a composição microbiana da rizosfera afetando as plantas que interagem com ela FuNNell-harris et al, 2008). Por outro lado, em alguns casos, micro-organismos da rizosfera podem favorecer a degradação de certos compostos alelopáticos diminuindo, assim, sua fitotoxicidade, particularmente nos casos de ácidos fenólicos.…”
Section: Produção De Sorgo No Brasilunclassified